2013
DOI: 10.1136/jclinpath-2013-201445
|View full text |Cite
|
Sign up to set email alerts
|

Faecal haemoglobin concentration is related to severity of colorectal neoplasia

Abstract: f-Hb is related to severity of colorectal neoplastic disease. This has ramifications for the selection of the appropriate cut-off concentration adopted for bowel screening programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
73
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 17 publications
(11 reference statements)
11
73
4
Order By: Relevance
“…Advanced colorectal neoplasia is associated with a higher FIT Hb concentration, and accordingly a higher Hb concentration leads to a higher positive predictive value for AN (27)(28)(29)(30). Th ese results are consistent with our fi ndings and this readily explains the relation between a high fecal Hb concentration and the need for a secondlook colonoscopy.…”
Section: Discussionsupporting
confidence: 90%
“…Advanced colorectal neoplasia is associated with a higher FIT Hb concentration, and accordingly a higher Hb concentration leads to a higher positive predictive value for AN (27)(28)(29)(30). Th ese results are consistent with our fi ndings and this readily explains the relation between a high fecal Hb concentration and the need for a secondlook colonoscopy.…”
Section: Discussionsupporting
confidence: 90%
“…Research has explored many basic aspects concerning f-Hb and it has been shown that f-Hb rises with age and is higher in men than in women (7,8), and higher in the more socioeconomically deprived (8,9). It has been well documented that higher f-Hb is associated with a higher incidence of CRC and advanced adenoma, that is, advanced neoplasia (AN), because f-Hb is directly related to the severity of colorectal disease (10). Thus, it is hardly surprising that, if FITs are used as a simple qualitative dichotomous investigation with a single cut-off f-Hb applied to all participants, as is done in almost all current CRC screening programmes, as the f-Hb cut-off applied is increased, positivity rate, AN detection rate and sensitivity decrease, while specificity, positive predictive value and interval cancer proportion increase.…”
Section: Fits For Haemoglobinmentioning
confidence: 99%
“…Added to this, when referral is made into secondary care following a positive FIT result, the quantitative result may allow those with elevated f-Hb more in keeping with malignancy to be triaged effectively8 since f-Hb is directly related to the severity of colorectal disease, with more significant bowel diseases (SBDs) being associated with higher f-Hb 9. Indeed, it has been suggested that the f-Hb could be used to prioritise further investigation, those with higher f-Hb being further investigated sooner 3 4.…”
Section: Introductionmentioning
confidence: 99%